Improving sunflower production and reducing post-harvest losses [Uganda] - Mlay, Felix (Technical Centre for Agricultural and Rural Cooperation, 2018)
A project in Singida, Tanzania, is working with smallholder producers to stimulate market-based agriculture. To increase the quantity and quality of products available for the market and address poverty in the region, the project focuses, in particular, on overcoming the barriers smallholders face to participating profitable in the sunflower market.